2017
DOI: 10.1111/phn.12344
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane preparedness among elderly residents in South Florida

Abstract: Findings are consistent with previous studies of samples drawn from similar populations. This report provides guidance as to how public health nurses can become involved with the population and develop interventions based on the constructs of the theoretical model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Motivating individuals and households to prepare for natural hazards has become an increasingly important strategy in emergency management since the mid-1990s (Ablah et al 2009 Only one full inventory was found for storm preparedness under the definition of storm used in this study and articulated below. This was developed and tested by Moon (2010) and further used by Kleier et al (2018) to measure influences on preparedness for a hurricane. Moon's (2010) inventory was based on a list of activities developed to measure earthquake preparedness by Paton , Smith, Johnston, Johnston and Ronan et al (2003), which they described as key performance indicators for assessing resilience and preparedness (Paton et al 2003, p. 28).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Motivating individuals and households to prepare for natural hazards has become an increasingly important strategy in emergency management since the mid-1990s (Ablah et al 2009 Only one full inventory was found for storm preparedness under the definition of storm used in this study and articulated below. This was developed and tested by Moon (2010) and further used by Kleier et al (2018) to measure influences on preparedness for a hurricane. Moon's (2010) inventory was based on a list of activities developed to measure earthquake preparedness by Paton , Smith, Johnston, Johnston and Ronan et al (2003), which they described as key performance indicators for assessing resilience and preparedness (Paton et al 2003, p. 28).…”
Section: Introductionmentioning
confidence: 99%
“…Moon's (2010) instrument, which was also used in association with other phenomenon of interest, such as motivations and vulnerabilities that might affect preparedness activity, showed relatively high internal consistency scores with Cronbach's alpha scores ranging from .731 to .881 (n =153 153) (Moon 2010, p. 73). Kleier et al (2018) reported a Cronbach's alpha score of their preparedness scale of .90 (n =147 147). Some studies have included a small number (nine or fewer) preparedness questions to measure preparedness in conjunction with measurement of some other phenomena in studies of tornado (Chaney et al 2013) and hurricane/cyclone (Sattler et al 2002;).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies focusing on the damage of extreme weather events and recovery plans for such events [3]- [7]. Some of the recent studies have investigated the impact of extreme weather conditions on vulnerable populations and searched for more efficient ways for emergency evacuation [6], [8]. Others have specifically performed disasters risk assessment [9], [10].…”
Section: Introductionmentioning
confidence: 99%